Integration of polysaccharide-thermoprotectant formulations for microencapsulation of Lactobacillus plantarum, appraisal of survivability and physico-biochemical properties during storage of spray dried powders. (May 2017) - Muhammad, Zafarullah; Ramzan, Rabia; Huo, Gui-Cheng; Tian, Hui; Bian, Xin
Abstract: The current study was carried out to validate that, potassium alginate (PA), pectin (P) and potato resistant starch (PRS) along with thermo protectants like maltodextrin, whey protein isolate (WPI) andd -mannose might deliver effective protection to probiotic Lactobacillus plantarum (KLDS 1.0344) cells during heat processing. Lowering of glass transition temperature improved the integrity of carrier medium during heat processing. Moreover, existence of polysaccharides not only, significantly decreased the collapse of the microcapsules but also, affected the particle size. Inactivation rate of the encapsulated KLDS 1.0344 cells followed first-order kinetics during storage. Composition of formulation materials like P and control contributed to maintain the water activity such as 0.25, 0.21 respectively, and might impacted the extension of shelf life of dried powders. PRS in combination with heat protective agents displayed better survival of probiotics during storage study by formation of stable coating film and higher moisture content. While, the P and PA provided the lower grade protection and exerted a negative impact as compared to control after simulated gastrointestinal digestion. Graphical abstract: Highlights: Physical properties of encapsulants might affect the probiotics survival. Samples with potato resistant starch showed practically resistance to sustain the survivability during digestion and storage. Potassium alginate and pectin gave relatively high post drying viable counts. Heat survivability was improved by the addition of thermoprotectants.